PROBLEM BASED LEARNING IN THE FACULTY OF MEDICINE – UNIVERSITY OF GEZIRA - abubakr, muzdalifa; Mirghani, Omer Ahmed; Mohamed, Mohamed Elsanousi (مجلة الجزيرة للعلوم الصحية; مجلد 3 عدد 1 (2007), 2007)
This article describes the main objectives of a medical school, how effective is problem based learning (PBL) in helping the student achieve the educational objectives of the faculty, the approach to PBL adopted by the Faculty of Medicine University of Gezira (FMUG).